The Role of Medication in Spontaneous Gastrocutaneous Fistula Closure - Thomas, Priscilla G.; Sharp, Nicole E.; Schnell, Katherine; Snyder, Charles L.; St Peter, Shawn D. (European Journal of Pediatric Surgery, 2015)
Purpose Factors precipitating persistence of gastrocutaneous fistulas (GCFs) are not clearly understood. The role of proton pump inhibitors (PPIs) or histamine receptor antagonists in GCF closure is not yet studied. We aimed to identify whether these medications influence spontaneous GCF closure.Methods Retrospective review was performed on children who underwent gastrostomy tube insertion and removal from January 2010 to February 2013. Spontaneous GCF closure rates and medication use during gastrostomy tube removal were investigated.Results Of the 97 patients included, 48 had spontaneous GCF closure, whereas 49 required operative closure. When comparing these two groups, no significant difference existed in spontaneous GCF closure rates among patients who were on ranitidine, PPIs, or both (p = 0.09, p = 0.83, p = 0.06 respectively). Spontaneous closure occurred more in older patients (2.7 ± 4.1 vs. 0.9 ± 1.6 years, p < 0.01) and in patients without fundoplication at time of tube insertion (12.5 vs. 30.6%, p = 0.05). There were more laparoscopic placements in the group that closed spontaneously (83 vs. 61%, p = 0.02). Mean gastrostomy tube presence was longer in patients who required surgery than those with spontaneous closures (18.7 ± 10.3 vs. 35.5 ± 36.6 months, p < 0.01).Conclusion Ranitidine or PPI use upon removal of gastrostomy tubes does not seem to facilitate spontaneous GCF closure in children.
Keywords: gastrocutaneous fistula; ranitidine; proton pump inhibitor; pediatric